ИНТЕГРАЦИЯ ЦИФРОВЫХ ИГР В ПРОЦЕССЕ ОБУЧЕНИЯ РОДНОМУ ЯЗЫКУ МЛАДШИХ ШКОЛЬНИКОВ - Каллибекова, Г.А. (SCIENCE and SOCIETY, 2025)
This article explores the integration of digital games into native language instruction for primary school students. It examines the theoretical foundations of game-based learning, including constructivism, motivation theory, and gamification. The pedagogical benefits of digital games - such as increased motivation, personalized learning, and the development of language and communication skills - are highlighted. Examples are provided of how digital games can be used to improve spelling, grammar, vocabulary, and both oral and written language abilities. The article concludes that digital games are an effective and innovative tool in native language education.
Keywords: constructivism; integration; digital games; personal development; primary school student; motivation theory; gamification; socialization; education; interaction between teachers and parents; value orientations; family